Organizacje turystyczne w Internecie - analiza porównawcza witryn - Chmielarz, Witold (Tourist Organizations in Internet - Comparison Analysis of the Websites, 2005)
The main goal of the article is identification and valuation of characteristics of websites in tourism branch. At the beginning of the text specific features of this branch are presented. Then, some results of analysis are introduced. In the final part there are some conclusions about application of Internet in tourism branch.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1081, s. 142-150